The Properties and Application of Carbon Nanostructures - Slepička, Petr; Hubáček, Tomáš; Kolská, Zdeňka; Trostová, Simona; Kasálková, Nikola Slepičková; Bačáková, Lucie; Švorčík, Václav (IntechOpen, 2013)
None